Erythrocyte oxidative stress is associated with cell deformability in patients with retinal vein occlusion. (11th October 2016) - Becatti, M.; Marcucci, R.; Gori, A. M.; Mannini, L.; Grifoni, E.; Alessandrello Liotta, A.; Sodi, A.; Tartaro, R.; Taddei, N.; Rizzo, S.; Prisco, D.; Abbate, R.; et al.
Abstract : Essentials Retinal vein occlusion (RVO), characterized by blood hyperviscosity, has an unclear pathogenesis. We aimed to find out if hemorheological profile is altered by oxidative stress in RVO patients. Red blood cell (RBC) oxidative stress is associated to whole blood viscosity and RBC deformability. Reactive oxygen species alter RBC membrane rigidity, playing a key role in RVO pathogenesis. Summary: Background: Retinal vein occlusion (RVO) is characterized by vision loss resulting from hypoperfusion and hypoxia of the retina. RVO pathogenesis is not yet fully understood, although blood hyperviscosity has been observed. Erythrocyte deformability plays a key role in determining blood viscosity, and it is critical to microvascular perfusion and oxygen delivery. It has been shown that oxidative stress‐induced erythrocyte membrane fluidity alterations are linked to the progression of cardiovascular diseases. Objectives: To determine whether erythrocytes from RVO patients show signs of oxidative stress, and whether this condition can modify the hemorheologic profile in these patients. Patients and Methods: We analyzed the entire hemorheologic profile and erythrocyte oxidative stress – reactive oxygen species (ROS) production and membrane lipid peroxidation – in 128 RVO patients and 128 healthy subjects, matched for age and sex. Fluorescence anisotropy was used to evaluate the fluidity of erythrocyte membranes. Results: In RVO patients, erythrocyte oxidative stress was present and positively correlated with whole blood viscosity and erythrocyte deformability. Multivariate linear regression analysis after adjustment for age, cardiovascular risk factors, medications, leukocyte number and mean corpuscular volume indicated that erythrocyte‐derived ROS and erythrocyte lipid peroxidation were significantly and positively correlated with erythrocyte membrane viscosity and deformability. Moreover, in vitro experiments demonstrated that ROS have a key role in erythrocyte membrane fluidity. Conclusions: Our findings indicate that erythrocyte oxidative stress plays a key role in the pathogenesis of RVO, and pave the way to new therapeutic interventions.